A cheminformatics and network pharmacology approach to elucidate the mechanism of action of Mycobacterium tuberculosis γ-carbonic anhydrase inhibitors - Manaithiya, Ajay; Bhowmik, Ratul; Bhattacharya, Kunal; Ray, Rajarshi; Shyamal, Sagar Singh; Carta, Fabrizio; Supuran, Claudiu T.; Parkkila, Seppo; Aspatwar, Ashok (Frontiers in Pharmacology, 2024)
Background: Mycobacterium tuberculosis (Mtb) carbonic anhydrases (CAs) are critical enzymes that regulate pH by converting CO2 to HCO3 -, essential for Mtb's survival in acidic environments. Inhibiting γ-CAs presents a potential target for novel antituberculosis drugs with unique mechanisms of action.Objective: This study aimed to explore the biological connections underlying Mtb pathogenesis and investigate the mechanistic actions of antituberculosis compounds targeting the Cas9 protein.We employed homology modeling and virtual screening to identify compounds with high binding affinities for Cas9 protein. This study used the homology modeling approach employing high-quality AlphaFold DB models for γ-CA. Furthermore, the systems biology approach was used for analyzing the mechanistic modeling of compounds, integrating data on genes, pathways, phenotypes, and molecular descriptors. Single-cell RNA sequencing was also conducted to profile gene expression.Results: Three compounds, F10921405, F08060425, and F14437079, potentially binding to Cas9 protein, have been identified. F10921405 and F08060425 showed significant overlap in their effects on pathways related to the immune response, while F14437079 displayed distinct mechanistic pathways. Expression profiling revealed high levels of genes such as PDE4D, ROCK2, ITK, MAPK10, and SYK in response to F1092-1405 and F0806-0425, and MMP2 and CALCRL in response to F1443-7079. These genes, which play a role in immune modulation and lung tissue integrity, are essential to fight against Mtb.The molecular relationship and pathways linked to the mentioned compounds give the study a holistic perspective of targeting Mtb, which is essential in designing specific therapeutic approaches. Subsequent research will involve experimental validation to demonstrate the efficacy of the promising candidates in Mtb infections.